Crystal structures and supramolecular interactions of prism[6]arene-based host–guest systems with dihalohexanes - Mickey Vinodh; Nour O. Abdeljaber; Fatemeh H. Alipour; Talal F. Al-Azemi (Acta Crystallographica Section E: Crystallographic Communications)
The crystal structures of the supramolecular systems formed by perethoxy prism[6]arene (PS6) with 1,6-dichlorohexane (HexCl2), C90H96O12·2C6H12Cl2, and 1,6-diiodohexane (HexI2), C90H96O12·2C6H12I2, are reported. PS6 encapsulates these linear dihaloalkanes, creating 1:1 host–guest systems (PS6·HexCl2 and PS6·HexI2). The structural details and host–guest intermolecular interactions within the crystal networks are presented and discussed. In both crystal structures, the prism[6]arene macrocycle adopts a distorted cuboid shape, with the guest positioned perpendicular to its main axis.